Anatomia Quantitativa e Degradação in vitro de Tecidos em Cultivares de Capim-Elefante (Pennisetum purpureum Schumach.) - Alves De Brito, Cláudio José Freixieiro [UNESP]; Rodella, Roberto Antonio [UNESP]; Deschamps, Francisco Carlos; Alquini, Yedo (My University, 1999)
In this research, the main histological changes that occurred in cultivars of elephant-grass (Pennisetum purpureum Schumach.) at three development stages were determined. The tissue degradation was evaluated after incubation in cattle ruminal fluid. The percentage of tissues presented in the stem, keel, leaf limbo and sheath were determined. The keel and the stem presented greater proportion of lignified tissues, while the leaf limbo presented higher amount of epidermal and non-lignified vascular tissues. The parenchymal tissue was found in minor proportion on the leaf sheath, mainly by the presence of aerenchyma, from the second collection. The proportion of lignified tissues increased with the grass maturity, being more accentuated in stems and limbo. Among the main changes, stand out the greater degradation area found for leaf sheath, even with the tissue become older. This was associated with the presence of aerenchyma found in the advanced development stages. The stomata propitiated intrude of the microorganisms in the most internal leaf tissues (mesofilo). The thickness and lignification of the cell walls occurred as the grass become older, getting along with the reduction in the tissue degradation area.
Quantitative Anatomy and in vitro Tissue Degradation in Elephant Grass (Pennisetum purpureum Schumach.) Cultivars
Keywords: Cell wall; Forage; Lignin; Plant anatomy; Ruminant; Tissue degradation